Modeling Parkinson’s Disease With the Alpha-Synuclein Protein - Gómez-Benito, Mónica; Granado, Noelia; García-Sanz, Patricia; Michel, Anne; Dumoulin, Mireille; Moratalla, Rosario (Frontiers in Pharmacology, 2020)
Alpha-synuclein (α-Syn) is a key protein involved in Parkinson’s disease (PD) pathology. PD is characterized by the loss of dopaminergic neuronal cells in the substantia nigra pars compacta and the abnormal accumulation and aggregation of α-Syn in the form of Lewy bodies. More precisely, the aggregation of α-Syn is associated with the dysfunctionality and degeneration of neurons in PD. Also, mutations in the SNCA gene, which encodes α-Syn, cause familial forms of PD and are the basis of sporadic PD risk. Given the role of the α-Syn protein in the pathology of PD, animal models that reflect the widespread and progressive formation of α-Syn aggregates in different areas of the brain constitute a valuable tool. Indeed, animal models of PD are important for understanding the molecular mechanisms of the disease and might contribute to the development and validation of new therapies. In the absence of animal models that faithfully reproduces human PD, in recent years, numerous animal models of PD based on α-Syn have been generated. In this review, we summarize the main features of the α-Syn pre-formed fibrils (PFFs) model and adeno-associated virus vector (AAV) mediated α-Syn overexpression models, providing a detailed comparative analysis of both models. Here, we discuss how each model has contributed to our understanding of PD pathology and the advantages and weakness of each of them.